The impact of helical slide honing on surface microtexture compared to plateau honing process through relevant characterization methods - Yousfi, Mohammed; Ţălu, Ştefan (Microscopy research and technique, 2022)
The cylinder engine surface texture has a major influence on the functional performances of the ring‐pack tribo‐system. The cylinder engine surface microtexture manufactured by plateau honing (PH) and helical slide honing (HSH) processes have been analyzed using white light interferometry (WLI), and stereometric analysis. The approaches in three‐dimensional (3‐D) white light interferometer measurements and surface stereometric analysis are important for the correct interpretation of 3‐D local surface texture features and can be applied in mathematical models for calculating the friction. The samples were divided into two groups: plateau honing (PH) samples and helical slide honing (HSH) samples to discuss the obtained results, according to the honing techniques obtained after several stages: the rough and finish honing and final stage. The obtained results demonstrated that the surface of group PH has the higher values of root mean square height (Sq = 1.83 μm) and fractal dimension (Df = 2.74 ± 0.01), while the lowest values of root mean square height (Sq = 0.63 μm) and fractal dimension (Df = 2.60 ± 0.01) were found for HSH samples. These values highlight that the PH samples are more irregular (both as surface and topography) in comparison with HSH samples. Highlights We characterized the micromorphology of surface microtexture in plateau and helical slide honing. The nanostructure morphology was investigated using the white light interferometry, fractal and stereometric analyses. The surface topography during the HSH process has different characteristics than the PH process and can be used to obtain better friction and lubrication performances. 2‐D and 3‐D micrographs of samples: (a) PH; (b) HSH.